The Contribution of Professional Development Programme on HOTS-oriented German Language Teaching - Rabbani, Talitha Ardelia Syifa (Riviera Publishing, 2025)
This study examines the contribution of a professional development program on Higher-Order Thinking Skills (HOTS)-oriented German language teaching. Conducted at a high school in Jakarta, Indonesia, the research focuses on a German teacher who participated in the HOTS-based Language Teaching Methodology Training. Using a descriptive case study approach, data were collected through questionnaires, classroom observations, and interviews. The findings reveal that while the teacher demonstrated an improved understanding of HOTS and its integration into language teaching post-training, challenges such as limited preparation time, inadequate teaching materials, and students' low German proficiency hindered optimal implementation. Classroom practices predominantly emphasized lower-order thinking skills (LOTS), with minimal application of HOTS-oriented learning models introduced in the training. However, the teacher employed strategies like cultural comparisons to foster critical thinking. Student perceptions indicated confidence in using German during class activities but limited motivation to apply it outside the classroom. The study highlights the need for better-prepared teaching materials, more training support, and adjustments to classroom dynamics to effectively integrate HOTS into German language instruction.